The Illustrated guide to the Bible - Porter, J.R. (Joshua Roy), 1921-2006 (New York : Chartwell Books, 2016)
"Examines the Biblical narratives in their historical, social, archaeological, and mythological contexts and provides a section with a book-by-book summary of the Bible.
Originally published: New York: Oxford University Press, 1995
Includes bibliographical references and index
Keywords: Bible -- History of biblical events; Bible -- Illustrations; Bible -- Introductions; Jews -- Civilization -- To 70 A.D.; Palestine -- Civilization